KETIDAKMERATAAN PEMBANGUNAN INFRASTRUKTUR DAERAH DAN DAMPAKNYA BAGI KESEJAHTERAAN MASYARAKAT DI KABUPATEN BANJARNEGARA - M, Yesie Cindra; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2019)
Regional autonomy is an authority that is given to autonomous regions to regulate and manage government affairs and the interests of the local community according to the aspirations of the community to increase the usability and also the results for the administration of government in the context of service to the community and implementation of legislation. But in the implementation of regional autonomy, not all regions can develop rapidly, so that there are several regions classified as still lagging behind. One of them is Banjarnegara Regency. To relinquish its status as a disadvantaged area, the Regency has carried out various development activities and infrastructures. So that in 2010 Banjarnegara District succeeded regardless of the status of underdeveloped regions. After being detached from the status of underdeveloped regions, until now Banjarnegara Regency is still continuing to carry out various development activities to strengthen the economy of the community. Ideal development must be fair and equitable. But in practice, infrastructure development in Banjarnegara Regency has not been evenly distributed. For this reason, this study will discuss the inequality of regional infrastructure development, especially road / bridge infrastructure, irrigation networks and markets. And its impact on people's welfare. The results of this study, the inequality of regional infrastructure development is because the existing development is only focused on the urban area. So that economic inequality is quite significant between urban areas and rural areas. Keywords: Infrastructure Development, Community Welfare, District Government